Actualización de la familia Verbenaceae en la Argentina con foco en sus patrones de diversidad - Moroni, Pablo Daniel (2024)
After more than a decade since the first publication of the treatment of the Verbenaceae family in the Flora Argentina project, this contribution offers an updated version of the taxonomic and nomenclatural changes that occurred since then. In this regard, a detailed list of the 170 species that inhabit the Argentine territory is presented, along with information on their distribution by province. Additionally, a generic key is provided, elaborated with useful morphological features for identification, accompanied by a discussion on the situation of each genus. Furthermore, for the first time, this work provides a critical and exhaustive analysis of the geographical distribution of Verbenaceae taxa in Argentina, considering the country’s historical-geographical and biotic areas. The compiled records indicate that the greatest diversity of Verbenaceae is primarily found above the 33° south latitude parallel, specifically in the xeric ecoregions of the northwest. As latitude increases, a decrease in diversity is observed, particularly pronounced in the Patagonia region, although with a notable proportion of restricted and endemic species.